XPS Study of the Chemical Structure of Plasma Biocopolymers of Pyrrole and Ethylene Glycol. (24th August 2014) - González-Torres, Maribel; Olayo, Ma. Guadalupe; Cruz, Guillermo J.; Gómez, Lidia Ma.; Sánchez-Mendieta, Víctor; González-Salgado, Francisco
Abstract : An XPS study about the structure of plasma biocopolymers synthesized with resistive radio frequency glow discharges and random combinations of ethylene glycol, pyrrole, and iodine, as a dopant, is presented in this work. The collisions of molecules produced structures with a great variety of chemical states based in the monomers, their combinations, crosslinking, doping, fragmentation, and oxidation at different levels in the plasma environment. Iodine appears bonded in the copolymers only at high power of synthesis, mainly as C–I and N–I chemical bonds. Multiple bonds as C ≡ C, C ≡ N, C=O, and C=N were found in the copolymers, without belonging to the initial reagents, and were generated by dehydrogenation of intermediate compounds during the polymerization. The main chemical states on PEG/PPy/I indicate that all atoms in pyrrole rings participate in the polymerization resulting in crosslinked, partially fragmented, and highly oxidized structures. This kind of analysis can be used to modify the synthesis of polymers to increase the participation of the most important chemical states in their biofunctions.